(untitled) (The Research of Medical Science Review, 2025)
Polypharmacy, which is the use of multiple medications at the same time, is an important issue, especially for ageing individuals who have various diseases. Therefore, as applicable for chronic diseases, high medication use comes with consequences such as adverse drug reactions, drug-drug interactions, cognitive decline, and hospitalizations. Family physicians have a great opportunity to enhance the proper use of medication through deprescribing, a purposeful approach to discontinuation of unnecessary medications. This paper aims to discuss polypharmacy as an issue, deprescribing supported by evidence, and the involvement of family physicians regarding safe prescribing. It also looks at another next level of intervention, such as deprescribing initiatives at a national level, insurance reimbursement for medication review, and technology-enhanced optimization. However, specific challenges, like healthcare provider resistance, patient resistance, and poorly defined protocols, pose obstacles to deprescribing. Polypharmacy has to be approached from a patient and clinician-team perspective at the individual patient level, with decision-support clinical tools and policy facilitating this process.